2009
DOI: 10.1186/1742-4682-6-7
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Murray's law using a non-Newtonian model of blood flow

Abstract: Background: So far, none of the existing methods on Murray's law deal with the non-Newtonian behavior of blood flow although the non-Newtonian approach for blood flow modelling looks more accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 29 publications
8
71
1
2
Order By: Relevance
“…This applies also to stress situations: when a higher rate of blood (or sap) flow is needed, the existence (or the emergence) of a self-regulatory response which suitably adjusts the vessels radii, as originally proposed by Hess, seems reasonable [15]; (h) The H-M law also allows for an "allometric scaling" between different species [20]: if the relative sizes of the respective blood (or sap) vessels scale according to this law, then the physical dimensions depend on the radius of the main branch, which in turn depends on the metabolic rate of the species [21]; (i) If blood is modelled as a non-Newtonian fluid, the 2´1 /3 law does not apply anymore, because-as expected-the exponent is found to have a non negligible dependence on the viscosity law (from 1 to 2.5 in [22,23]). Miguel [17,18] analyzed the irreversibility in branched flows of a power fluid and showed that (a) the "optimal" radius ratio depends on the "degree of non-newtonianity" of the fluid, ω; (b) that in the limit of Newtonian behavior, ω tends to 1 and the H-M law is recovered; (j) It is also possible to derive the optimal radius ratio in a dendritic structure by reformulating the problem as a constrained multi-variable optimization [11,24,25]: this approach, useful as it may be in engineering applications, loses somewhat of its significance in biological investigations.…”
Section: A Brief Summary Of Experimental Results and Of Other Allometmentioning
confidence: 93%
“…This applies also to stress situations: when a higher rate of blood (or sap) flow is needed, the existence (or the emergence) of a self-regulatory response which suitably adjusts the vessels radii, as originally proposed by Hess, seems reasonable [15]; (h) The H-M law also allows for an "allometric scaling" between different species [20]: if the relative sizes of the respective blood (or sap) vessels scale according to this law, then the physical dimensions depend on the radius of the main branch, which in turn depends on the metabolic rate of the species [21]; (i) If blood is modelled as a non-Newtonian fluid, the 2´1 /3 law does not apply anymore, because-as expected-the exponent is found to have a non negligible dependence on the viscosity law (from 1 to 2.5 in [22,23]). Miguel [17,18] analyzed the irreversibility in branched flows of a power fluid and showed that (a) the "optimal" radius ratio depends on the "degree of non-newtonianity" of the fluid, ω; (b) that in the limit of Newtonian behavior, ω tends to 1 and the H-M law is recovered; (j) It is also possible to derive the optimal radius ratio in a dendritic structure by reformulating the problem as a constrained multi-variable optimization [11,24,25]: this approach, useful as it may be in engineering applications, loses somewhat of its significance in biological investigations.…”
Section: A Brief Summary Of Experimental Results and Of Other Allometmentioning
confidence: 93%
“…In this study, a Newtonian fluid model is considered to describe the rheology of blood and Murray's principle of energy minimization is effectively used. The validity of the classical Murray's law using a Power law model of blood flow in a rigid arterial bifurcation is demonstrated by Revellin et al [8]. The energy expenditure by the wall of blood vessel (the metabolic state of blood vessel wall) has not been taken into account in papers [3][4][5][6][7][8], which will be realistic to be considered in the sense that with smaller vessels, where introduction of such an optimality principle will in general be best met, the proportion of the thickness of the vessel wall to the vessel size is known to become greater.…”
Section: Introductionmentioning
confidence: 96%
“…Such constraints widely exist in electricity [1] , nuclear physics [2] , biology [3][4] , bifurcation control [5][6] , model interaction [7] , non-smooth dynamics [8] , etc. Only using the unconstrained singularity theory, one cannot get all the bifurcation types of a constrained bifurcation, and thus one cannot master bifurcation behaviors on the whole [7][8] .…”
Section: Introductionmentioning
confidence: 99%